Characterising Charm Jet Properties with Azimuthal Correlations of D Mesons and Charged Particles with ALICE at the LHC - Shyam Kumar (Proceedings, 2019)
Charm quarks are produced via hard parton scattering in ultra-relativistic heavy-ion collisions, hence are ideal probes to study a possible de-confined state of matter, known as Quark Gluon Plasma (QGP). The angular correlation of a meson containing a charm quark with other charged particles in heavy-ion collisions can help in studying the properties of QGP. Similar studies in pp collisions can give insight about the charm production mechanism while in p-Pb collisions could provide essential information to disentangle final-state QGP-induced modifications from effects caused by cold nuclear matter. In this proceedings, the results are presented for p-Pb collisions at <semantics> <msqrt> s NN </msqrt> </semantics> = 5.02 TeV and pp collisions at <semantics> <msqrt> s </msqrt> </semantics> = 13 TeV, so far the highest available energy at the LHC. The results are compared with Monte Carlo (MC) simulations using PYTHIA and POWHEG event generators and with pp collision results at <semantics> <msqrt> s </msqrt> </semantics> = 7 TeV.